Evaluasi Rasionalitas Tepat Pasien dan Tepat Indikasi Pasien Rawat Jalan Diabetes Melitus Tipe 2 di RSUD Tabanan - I Wayan Weda Aryawan; Putu Ika Indah Indraswari; Pande Made Ayu Aprianti (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Type 2 Diabetes Mellitus (DM) is a disease caused by impaired insulin function, impaired insulin secretion, or both, resulting in a hyperglycemic condition. Patients with type 2 DM generally exhibit characteristics such as a Random Blood Glucose level exceeding 200 mg/dL and an HbA1c level exceeding 6.5%. The accuracy of medication administration to patients must also consider the rationality of antidiabetic therapy in order to influence the success rate of optimal therapy. This study aims to evaluate the rationality of patient appropriateness and indication appropriateness in outpatients with type 2 DM at Tabanan Regional Public Hospital (RSUD Tabanan). This study employed a semi-quantitative observational research design with a retrospective approach by reviewing patient medical records from the initiation of therapy. Sampling was conducted using purposive sampling, whereby samples had to meet predetermined inclusion criteria. The results indicated that the age group with the highest prevalence of DM patients at RSUD Tabanan was over 56 years old (74%), with a predominance of females (63%). The most common comorbidity among DM patients was hypertension alone (24.5%). Based on the findings, the percentage of patient appropriateness rationality among DM outpatients at RSUD Tabanan was 97.5%, while the percentage of indication appropriateness rationality in type 2 DM outpatients at RSUD Tabanan was 98.5%.